Respostas
respondido por:
1
Resposta:
3. x + 6
--------- = ------------
x - 4. 2x
2x(3). (x+6)(x-4)
----------- = ---------------
2x(x-4). 2x(x-4)
6x = x² -4x + 6x - 24
x² - 4x + 6x - 6x - 24 = 0
x² -4x - 24 = 0
x = -b ± √ b² - 4 a b
-------------------------
2 a
x = -(-4)±√(-4)²-4(1)(-24)
----------------------------------
2• 1
x = 4 ± √16 + 96
---------------------
2
x = 4 ± √112
----------------
2
x = 2 ± √112
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás